Successful Pregnancies after the Treatment of a Thymic Carcinoid - Wiebren A. A. Tjalma (Hindawi Limited, 2015)
The present report describes the case of a woman diagnosed with an adrenocorticotropic hormone- (ACTH-) secreting thymic carcinoid associated with Cushing's syndrome. Treatment consisted of tumour resection and 131-I-meta-iodobenzylguanidine (MIBG) therapy. In spite of her iatrogenic menopausal state she twice became pregnant and delivered two healthy babies but developed recurrences during both pregnancies. The last recurrence presented as a primary breast cancer. Despite poor prognosis our patient survived for eleven years. To our knowledge this is the first report of successful pregnancy and delivery in a patient with a thymic carcinoid.